Bioinformatics and functional genomics - Jonathan Pevsner (Wiley-Blackwell, 2009)
Access to sequence data and literature information -- Pairwise sequence alignment -- Basic local alignment search tool (BLAST) -- Advanced database searching -- Multiple sequence alignment -- Molecular phylogeny and evolution -- Bioinformatic approaches to ribonucleic acid (RNA) -- Gene expression : microarray data analysis -- Protein analysis and proteomics -- Protein structure -- Functional genomics -- Completed genomes -- Completed genomes : viruses -- Completed genomes : bacteria and archaea -- The eukaryotic chromosome -- Eukaryotic genomes : fungi -- Eukaryotic genomes : from parasites to primates -- Human genome -- Human disease.